Bidirectional control of the inner dynamics of focal adhesions promotes cell migration - Goetz, Jacky G (Landes Bioscience, 2009)
Focal adhesions (FA) are bidirectional mechanical biosensors that allow cells to integrate intracellular and extracellular cues. Their function is tightly regulated by changes in molecular composition and also by variation in the spatio-temporal dynamics of FA components within this structure. A closely regulated turnover of FA proteins within FA sites allows cells to respond appropriately to their environment, thereby impacting on cell shape and function. FA protein dynamics are linked to FA maturation and rates of assembly and disassembly, and have a significant influence on tumor cell migration. Using the FRAP technique to investigate the hidden internal dynamics of FA, we identified two new regulators of FA dynamics and cell migration: the Mgat5/galectin-3 lattice and tyrosine phosphorylated caveolin-1 (pY14Cav1). In this short review we first introduce FA and their complex dynamic behavior. We then present the Mgat5/galectin-3 lattice and caveolin-1 and discuss their concerted role in FA dynamics, which defines previously unknown, interdependent roles in tumor cell migration. We conclude with a discussion of interesting unexplored avenues that might lead to a better understanding of the complex mechanism of FA dynamics.